(untitled) (Indian Journal of Veterinary Pathology, 2025)
A 6 year old pregnant goat was presented with the complaint of straining for one day. The animal has completed the gestation period. The c-section was performed and three kids were delivered, out of which one was alive and two were dead. The dead kids were brought to postmortem and necropsy was conducted. The animals showed pale, thickened skin with myxedema and devoid of hair from the body. The thryoid glands of both animals were enlarged bilaterally. Grossly the enlarged thyroid gland was red and hard in consistency and free from any attachment in the neck region. Histopathologically, various sizes of thyroid follicles filled with colloid and hyper cellularity or c-cell hyperplasia and complete absence of absorption vacuoles were observed. On the basis of gross and histopathology, the case was diagnosed as bilaterally diffused congenital goitre in kids.